PENGEMBANGAN MEDIA ARABIC HOLE BERBASIS VISUAL DALAM PEMBELAJARAN MAHARAH QIRA’AH SISWA KELAS XI MADRASAH ALIYAH AL BAIRUNY SAMBONGDUKUH JOMBANG TAHUN AJARAN 2019/ 2020 - Rizqi Fatmawati (LPPM Universitas KH. A. Wahab Hasbullah, 2019)
Arabic is a foreign language that is widely studied in Indonesia. But in learning Arabic, there are so many problems faced by students when learning Arabic. Among the low student interest in learning, there is an assumption that learning Arabic is a difficult thing and the limited learning media of Arabic so learning feels monton and boring. From these problems, researchers developed a learning media in the form of Arabic Hole board games to increase student motivation and facilitate student understanding. The researcher uses a research and development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Conducting small trials and field trials to improve students' learning motivation in class XI at MA Al Bairuny Sambongdukuh Jombang using Arabic Hole media. The results obtained are the influence of the media on students' learning abilities especially in reading skills (Maharah Qira’ah).